Using e-Learning as a Tool for Enhancing Teaching and Learning in University Education: Lessons Learned from Machakos and Chuka Universities - Koech, Peter Kibet; Wanjiku, Kang’ara Hannah (Machakos University Press, 2022)
This paper argues that e-learning is a critical component in teaching and learning especially during the Covid-19 pandemic. The paper interrogates the online teaching and learning environments, the Moodle as an e-learning platform for teaching and learning, the challenges of using e-learning in teaching and learning, and the effect of E-Learning on University Education. This paper also provides some practical lessons on e-learning from Machakos and Chuka Universities. The study adopted a desk review approach that focuses on document analysis to get information on e-learning. The documents analyzed were journals, Internet Communication and Technology (ICT) websites, and paper reviews on online teaching and learning. Also, interviews of OdeL staff in the two universities was done The paper concludes that e-Learning can be adopted and utilized to promote education in Africa even during covid-19 pandemic times and post Covid era. In addition, e-learning can make learning easier and accessible to everyone, everywhere in the world. It provides the opportunity to achieve great results at lower costs and thus revolutionizing the conventional education system.
Keywords: Online teaching; Moodle as an e-learning platform; Challenges; Effect of E-Learning